2019
DOI: 10.5539/apr.v11n1p52
|View full text |Cite
|
Sign up to set email alerts
|

Negative Ion Formation in Low-Energy Electron Collisions with the Actinide Atoms Th, Pa, U, Np and Pu

Abstract: Here we investigate ground and metastable negative ion formation in low-energy electron collisions with the actinide atoms Th, Pa, U, Np and Pu through the elastic total cross sections (TCSs) calculations. For these atoms, the presence of two or more open d-and f-subshell electrons presents a formidable computational task for conventional theoretical methods, making it difficult to interpret the calculated results. Our robust Regge pole methodology which embeds the crucial electron correlations and the vital c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
38
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(43 citation statements)
references
References 39 publications
5
38
0
Order By: Relevance
“…In the lanthanide and actinide atoms, in particular the presence of two or more open d-and f-subshell electrons presents formidable computational complexity when using conventional theoretical methods to calculate electron affinities (EAs) of complex heavy systems. Thus, recent years have witnessed the proliferation in the published literature of incorrect experimental and theoretical EAs for the lanthanide [2] and actinide [3] atoms as well as for atomic Nb. For the complex atoms such as Nb experiments have concentrated efforts mainly on the accuracy rather than on the reliability of the existing EAs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the lanthanide and actinide atoms, in particular the presence of two or more open d-and f-subshell electrons presents formidable computational complexity when using conventional theoretical methods to calculate electron affinities (EAs) of complex heavy systems. Thus, recent years have witnessed the proliferation in the published literature of incorrect experimental and theoretical EAs for the lanthanide [2] and actinide [3] atoms as well as for atomic Nb. For the complex atoms such as Nb experiments have concentrated efforts mainly on the accuracy rather than on the reliability of the existing EAs.…”
Section: Introductionmentioning
confidence: 99%
“…(5) Very recently, electron scattering TCSs for the very complicated actinide atoms Th, Pa, U, Np and Pu were calculated [3]. It was concluded that the existing theoretical calculations tend to identify incorrectly the BEs of the resultant excited anionic states with the EAs of the investigated actinide atoms; this suggests a need for an unambiguous definition and determination of the EAs.…”
Section: Introductionmentioning
confidence: 99%
“…In Figure 1 , the standard elastic TCSs for the Au and C 60 systems taken from [ 32 ] are displayed. They reveal the important characteristic negative ion BEs, R–T minima and shape resonances.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, calculated low-energy electron elastic TCSs are characterized by dramatically sharp resonances that manifest ground, metastable and excited negative ion formation, with the ground state binding energies (BEs) yielding the important EAs that are theoretically challenging to calculate for complex heavy systems. In Figure 1, the standard elastic TCSs for the Au and C 60 systems taken from [32] are displayed. They reveal the important characteristic negative ion BEs, R-T minima and shape resonances.…”
Section: Electron Scattering Total Cross Sections and Electron Affinimentioning
confidence: 99%
“…In Fig. 1 the standard elastic TCSs for the Au and C 60 systems taken from [32], are displayed. They reveal the important characteristic negative ion BEs, R-T minima and shape resonances.…”
Section: Electron Scattering Total Cross Sections and Electron Affinimentioning
confidence: 99%